2016
DOI: 10.1136/gutjnl-2015-310710
|View full text |Cite
|
Sign up to set email alerts
|

The TRPA1 ion channel is expressed in CD4+ T cells and restrains T-cell-mediated colitis through inhibition of TRPV1

Abstract: Objective Transient Receptor Potential Ankyrin-1 (TRPA1) and Vanilloid-1 (TRPV1) are calcium (Ca2+)-permeable ion channels mostly known as pain receptors in sensory neurons. However, growing evidence suggests their crucial involvement in the pathogenesis of IBD. We explored the possible contribution of TRPA1 and TRPV1 to T cell-mediated colitis. Design We evaluated the role of Trpa1 gene deletion in two models of experimental colitis (i.e., interleukin-10 knockout and T cell adoptive transfer models). We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 47 publications
2
126
2
Order By: Relevance
“…A current study [46] demonstrated that TPRA1-/-CD4+ T cells have increased T-cell receptor-induced Ca 2+ influx, activation profile and subsequent differentiation into Th1-effector cells. The study suggests a protective role of TRPA1 in T-cellmediated colitis as well as activation by GA of a non-selective cation current in lymphocytes that could contribute to a decrease in IL-α production.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…A current study [46] demonstrated that TPRA1-/-CD4+ T cells have increased T-cell receptor-induced Ca 2+ influx, activation profile and subsequent differentiation into Th1-effector cells. The study suggests a protective role of TRPA1 in T-cellmediated colitis as well as activation by GA of a non-selective cation current in lymphocytes that could contribute to a decrease in IL-α production.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Our results suggest that TRPA1 plays an important role relevant for T cell activation, likely by different endogenous factors. In a recent report, the functional expression of TRPA1 in murine and human CD4 + T cells has been shown to regulate T cell activation and pro-inflammatory responses [20]. However, the previous reports have suggested a proinflammatory role of TRPA1 towards immune activation and inflammation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recently it has been reported that CD4 + T cell-associated TRPA1 may regulate inflammation in experimental colitis model in mice [20]. However, evidence for any such functional requirement of TRPA1 in T cell responses, in vitro, remains scanty.…”
Section: Discussionmentioning
confidence: 99%
“…Icilin is described as a superagonist of TRPM8, but can also reportedly activate TRPA1 at higher concentrations (31,32). As TRPA1 is functionally expressed in lymphocyte populations and plays a key inhibitory role in CD4 + T-cell responses (33), we sought to determine whether the effect of icilin on T-cell proliferation was dependent on either TRPM8 or TRPA1. Consistent with icilin exerting its protective role in EAE in a TRPM8independent fashion (Fig.…”
Section: Icilin Induces a Dose-dependent Reduction In Cd4 + T-cell Prmentioning
confidence: 99%